Hollow silicon dioxide microsphere and preparation method thereof
By using grafting reaction and click chemical reaction methods in the preparation of hollow silica microspheres, a core-shell structure precursor with silica coated polymer is formed, which solves the problems of high cost, complex process and poor stability in traditional methods, and achieves controllability and efficient preparation of microspheres.
Patent Information
- Application Number
- CN202411756459.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
The traditional hollow silica sphere preparation method has problems such as high cost, complex process and poor stability, making it difficult to achieve controllability of the size, wall thickness and density of microspheres.
By mixing the aqueous solution of the polymer, azide salt, initiator and organic solvent for grafting reaction, an azide modified polymer was obtained, and a click chemical reaction was carried out with a silane containing alkynyl under the action of a click chemical catalyst to form a core-shell structure precursor of silica coated polymer, and then hollow silica microspheres were obtained by calcination or solvent extraction.
The hollow silica microspheres are simple in process, low in cost and high efficiency, and can accurately regulate the size, wall thickness and density of microspheres to meet the needs of different application fields.
Smart Images

Figure CN119612526A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new materials technology, and in particular to a hollow silica microsphere and its preparation method. Background Technology
[0002] Hollow silica microspheres have broad application prospects in catalysis, adsorption, and biomedicine due to their advantages such as low density, high surface area, and good thermal insulation properties. However, traditional methods for preparing hollow silica microspheres, such as template methods, self-assembly, and spray drying, all suffer from limitations such as high cost, complex processes, and poor stability.
[0003] Therefore, there is an urgent need for a preparation method that is simple in process, low in cost, and can achieve controllable size, wall thickness and density of microspheres. Summary of the Invention
[0004] Therefore, it is necessary to address the above-mentioned problems by providing a hollow silica microsphere and its preparation method. The preparation method provided by this invention is simple, low-cost, and highly efficient, and can effectively control the particle size, wall thickness, and density of the obtained hollow silica microspheres, thus having broad application prospects.
[0005] This invention provides a method for preparing hollow silica microspheres, comprising the following steps:
[0006] An aqueous solution of the polymer, an azide salt, an initiator, and an organic solvent are mixed to carry out a grafting reaction to obtain an azide-modified polymer. The azide-modified polymer is then added to a polar solvent to obtain a solution of the azide-modified polymer.
[0007] The alkynyl-containing silane, the azide-modified polymer solution, and the click chemistry catalyst are mixed and a click chemistry reaction is carried out. Then, an acid catalyst or a base catalyst is added to carry out a hydrolysis-condensation reaction to obtain a core-shell structure precursor of silica-coated polymer.
[0008] The core-shell structure precursor is subjected to calcination or solvent extraction to obtain hollow silica microspheres.
[0009] In one embodiment, in the grafting reaction, the molar ratio of the polymer to the azide salt, the initiator, and the organic solvent is 1:(0.5-300):(0.1-500):(50-2000);
[0010] And / or, in the reaction system of the grafting reaction, the concentration of the polymer is 10 mol / L to 1000 mol / L.
[0011] In one embodiment, the concentration of the azide-modified polymer in the solution is 1 g / L to 10 g / L.
[0012] In one embodiment, the polymer is selected from at least one of polymethyl methacrylate, polystyrene, polyethylene glycol, polyethyleneimine, and polyvinyl alcohol;
[0013] And / or, the initiator is selected from at least one of potassium persulfate, ammonium persulfate, and benzoyl peroxide;
[0014] And / or, the organic solvent is selected from at least one of acrylic acid, polymethyl methacrylate and styrene;
[0015] And / or, the polar solvent is selected from at least one of water, ethanol, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, and dichloromethane.
[0016] In one embodiment, in the click chemistry reaction, the molar ratio of the azide-modified polymer to the alkynyl-containing silane and the catalyst is 1:(0.1-20):(0.001-0.1).
[0017] In one embodiment, the molar ratio of azide functional groups to alkynyl functional groups in the click chemistry reaction is 1:0.1 to 1:50.
[0018] In one embodiment, the alkynyl-containing silane is selected from at least one of 1-(trimethylsilyl)propyne, bis(trimethylsilyl)acetylene, and alkynyl polyethylene glycol silane;
[0019] And / or, the click chemical catalyst is selected from copper salts, copper complexes, ruthenium complexes, ruthenium, and azide activators.
[0020] In one embodiment, the click chemistry catalyst is selected from at least one of CuSO4, CuCl2, bis(benzotriazol-1-yl)cuprous oxide, tri(benzotriazol-1-ylmethyl)amine-copper, dicyclohexenylruthenium dichloride, triphenylphosphine, and ruthenium.
[0021] In one embodiment, the grafting reaction is carried out at a temperature of 25°C to 90°C for a duration of 2 hours to 12 hours.
[0022] And / or, the temperature of the click chemical reaction is 20℃~30℃, and the time is 12h~24h;
[0023] And / or, the calcination treatment is carried out at a temperature of 500℃ to 600℃ for a time of 2h to 4h.
[0024] The present invention also provides hollow silica microspheres prepared by the preparation method described above.
[0025] The above preparation method involves a click chemical reaction between an azide-modified polymer and a silane-containing alkyne group under the action of a catalyst, effectively connecting the polymer and silane. The resulting molecular chain has a polymer chain at one end and a silane chain at the other end. Through polymer single-chain folding technology, the chemical anchoring, electrostatic, and hydrogen bonding forces between functional groups such as hydrophobic groups in the molecular chain are used to induce the molecular chain to fold and form a hollow structure. A core-shell structure precursor of silica-coated polymer is formed through a hydrolysis-condensation reaction. Removing the polymer yields hollow silica microspheres.
[0026] The preparation method provided by this invention is characterized by mild conditions, simple process, low energy consumption, low cost, and high preparation efficiency. At the same time, it can precisely control the size, wall thickness, and density of the microspheres, effectively realizing the controllable preparation of hollow silica microspheres, which can meet the needs of different application fields. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 This is a SEM image of the hollow silica microspheres prepared in Example 1 of the present invention;
[0029] Figure 2 This is a TEM image of the hollow silica microspheres prepared in Example 1 of the present invention;
[0030] Figure 3 The figures show the nitrogen adsorption-desorption curves and pore size distribution of the hollow silica microspheres prepared in Example 1 of this invention. Figure 3 (a) is the nitrogen adsorption-desorption curve of the hollow silica microspheres prepared in Example 1 of the present invention. Figure 3 (b) is a pore size distribution diagram of the hollow silica microspheres prepared in Example 1 of the present invention;
[0031] Figure 4 This is a TEM image of the product obtained in Comparative Example 1 of the present invention. Detailed Implementation
[0032] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0034] Through long-term and in-depth research, the applicant has discovered that polymer single-chain folding technology is a technique that utilizes intermolecular or intramolecular interactions to induce polymer chains to fold autonomously into three-dimensional structures. Among these, the technique utilizing intramolecular interactions to achieve single-chain folding can be achieved by introducing hydrophobic groups onto the polymer chain, utilizing chemical anchoring, electrostatic, and hydrogen bonding forces to induce the polymer single-chain folding into a hollow structure. This is a highly promising strategy for preparing hollow silica microspheres. Therefore, the hollow silica microspheres provided by this invention include the following steps:
[0035] This invention provides a method for preparing hollow silica microspheres, comprising the following steps:
[0036] S1. Mix the aqueous solution of the polymer, the azide salt, the initiator and the organic solvent, and carry out a grafting reaction to obtain the azide-modified polymer. Then, add the azide-modified polymer to a polar solvent to obtain a solution of the azide-modified polymer.
[0037] S2. Mix the alkynyl-containing silane, the azide-modified polymer solution, and the click chemistry catalyst to carry out a click chemistry reaction. Then, add an acid catalyst or a base catalyst to carry out a hydrolysis-condensation reaction to obtain a core-shell structure precursor of silica-coated polymer.
[0038] S3. The core-shell structure precursor is subjected to calcination or solvent extraction to obtain hollow silica microspheres.
[0039] The above preparation method involves a click chemical reaction between an azide-modified polymer and a silane-containing alkyne group under the action of a catalyst, effectively connecting the polymer and silane. The resulting molecular chain has a polymer chain at one end and a silane chain at the other end. Through polymer single-chain folding technology, the chemical anchoring, electrostatic, and hydrogen bonding forces between functional groups such as hydrophobic groups in the molecular chain are used to induce the molecular chain to fold and form a hollow structure. A core-shell structure precursor of silica-coated polymer is formed through a hydrolysis-condensation reaction. Removing the polymer yields hollow silica microspheres.
[0040] The preparation method provided by this invention is characterized by mild conditions, simple process, low energy consumption, low cost, and high preparation efficiency. At the same time, it can precisely control the size, wall thickness, and density of the microspheres, effectively realizing the controllable preparation of hollow silica microspheres, which can meet the needs of different application fields.
[0041] In step S1, azide groups are introduced into the polymer molecular chain through grafting modification, and the grafting reaction is highly efficient.
[0042] Preferably, the molar ratio of the polymer to the azide salt, the initiator, and the organic solvent is 1:(0.5-3000):(0.1-500):(50-2000), which is beneficial to increasing the reaction rate of the grafting reaction.
[0043] Specifically, in the reaction system of the grafting reaction, the concentration of the polymer is 10 mol / L to 1000 mol / L.
[0044] Preferably, the polymer is selected from at least one of polymethyl methacrylate, polystyrene, polyethylene glycol, polyethyleneimine, and polyvinyl alcohol.
[0045] Preferably, the initiator is selected from at least one of potassium persulfate, ammonium persulfate, and benzoyl peroxide, which is beneficial to increasing the reaction rate of the grafting reaction.
[0046] Preferably, the organic solvent is selected from at least one of acrylic acid, polymethyl methacrylate, and styrene, which is beneficial to improving mass transfer efficiency and thus further increasing the reaction rate of the grafting reaction.
[0047] Specifically, the grafting reaction is carried out at a temperature of 20°C to 90°C for a duration of 2 hours to 12 hours.
[0048] Preferably, the polymer is mixed with water and heated to 70°C to 90°C to obtain an aqueous solution of the polymer with a concentration of 5% to 10% (w / V). The initiator and the organic solvent are then added to the aqueous solution and mixed, followed by the addition of the azide to carry out the grafting reaction.
[0049] More preferably, when adding the azide, stirring is performed at a speed of 200 rpm to 400 rpm.
[0050] It should be noted that the azide is selected from sodium azide, potassium azide, etc., and the present invention does not have any special limitations on this.
[0051] In one embodiment, after the grafting reaction, the reaction system is cooled, cleaned, and dried to obtain an azide-modified polymer, and the azide-modified polymer is dissolved in a polar solution to improve the stability of the azide-modified polymer.
[0052] Specifically, the drying temperature is 40°C to 60°C.
[0053] Preferably, the polar solvent is selected from at least one of water, ethanol, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, and dichloromethane.
[0054] In one embodiment, the concentration of the azide-modified polymer in the solution is 1 g / L to 10 g / L.
[0055] In step S2, an alkyne-containing silane and an azide-modified polymer solution undergo a click chemical reaction under the action of a click chemistry catalyst, effectively connecting the polymer and the silane. The resulting molecular chain has a polymer chain at one end and a silane chain at the other end. The molecular chain is folded to form a hollow structure through chemical anchoring, electrostatic, and hydrogen bonding forces between its hydrophobic functional groups. Subsequently, an acid catalyst or a base catalyst is added to cause the silane to undergo a hydrolysis-condensation reaction, resulting in a core-shell structure precursor of the polymer coated with silica.
[0056] In one embodiment, in the click chemistry reaction, the molar ratio of the azide-modified polymer to the alkynyl-containing silane and the catalyst is 1:(0.1-20):(0.001-0.1).
[0057] In one embodiment, the molar ratio of azide functional groups to alkynyl functional groups in the click chemistry reaction is 1:0.1 to 1:50, which is beneficial for promoting the click chemistry reaction and achieving effective linkage between the polymer and silane.
[0058] Preferably, the alkynyl-containing silane is added to the azide-modified polymer solution, and a click chemistry catalyst is added to mix and carry out a click chemistry reaction. After the reaction is completed, the reaction system is washed and dried to obtain a solid product.
[0059] In one embodiment, the temperature of the click chemical reaction is 20°C to 30°C, and the time is 12h to 24h.
[0060] Preferably, stirring the click chemical reaction system at a speed of 200 rpm to 400 rpm is beneficial to improving the reaction rate of the click chemical reaction.
[0061] Preferably, the drying temperature is 40°C to 60°C.
[0062] In one embodiment, the alkynyl-containing silane is selected from at least one of 1-(trimethylsilyl)propyne, bis(trimethylsilyl)acetylene, and alkynyl polyethylene glycol silane.
[0063] It should be noted that the alkynyl-containing silane of the present invention can be obtained commercially or by self-production. When the alkynyl-containing silane is obtained by self-production, the silane and organic solvent are added to a dry Erlenmeyer flask and stirred evenly. Then, a boron trifluoride diethyl ether complex catalyst is added, and the reaction mixture is mixed evenly at a stirring speed of 200 rpm / min to 400 rpm / min. The reaction is carried out at 40°C to 60°C for 6 h to 12 h, wherein the concentration of the boron trifluoride diethyl ether complex catalyst is 1% to 2% of the silane concentration. After the reaction is completed, the reaction system is cooled to room temperature and washed with deionized water to remove unreacted raw materials and by-products. Then, the reaction product is stirred with lithium aluminum hydride at room temperature for 4 h to 6 h, and then hydrolyzed in ice water. The organic layer is separated and removed to obtain the alkynyl-containing silane.
[0064] In one embodiment, the click chemical catalyst is selected from copper salts, copper complexes, ruthenium complexes, ruthenium, and azide activators.
[0065] Preferably, the click chemistry catalyst is selected from at least one of CuSO4, CuCl2, bis(benzotriazol-1-yl)cuprous oxide, tri(benzotriazol-1-ylmethyl)amine-copper (Cu(I)-TBTA), dicyclohexenylruthenium dichloride, triphenylphosphine, and ruthenium (Ru).
[0066] In one embodiment, the solid product obtained from the click chemical reaction is dispersed in water, and an acid catalyst or a base catalyst is added to cause the silane to undergo a hydrolysis-condensation reaction and solidify on the surface of the polymer. The reaction is carried out at 20°C to 30°C for 6 to 12 hours, and after washing and drying, a core-shell structure precursor of the silica-coated polymer is obtained.
[0067] It should be noted that the hydrolysis-condensation reaction is a prior art in the field, and both the acid catalyst and the base catalyst are commonly used catalysts in the field, which will not be elaborated upon below.
[0068] Preferably, the cleaning process involves washing three times with water and three times with ethanol.
[0069] Preferably, the drying temperature is 40°C to 60°C.
[0070] In step S3, the polymer in the core-shell structure precursor is removed by calcination or solvent extraction to obtain hollow silica microspheres.
[0071] Specifically, during the roasting process, the core-shell structure precursor is roasted in air.
[0072] Preferably, the calcination treatment is carried out at a temperature of 500℃ to 600℃ for 2 hours to 4 hours.
[0073] Specifically, during solvent extraction, the core-shell precursor is fully dissolved and immersed in acetone or tetrahydrofuran and stirred at 500 rpm / min for 12 hours to allow the acetone or tetrahydrofuran to fully penetrate into the polymer template and dissolve the polymer. After the polymer template is completely dissolved, the silica layer is removed and then washed with a large amount of deionized water to remove residual solvent and dissolved polymer. Finally, the washed silica layer is dried to obtain hollow silica spheres.
[0074] The present invention also provides hollow silica microspheres prepared by the preparation method described above, wherein the particle size, wall thickness and density of the hollow silica microspheres are controllable and have broad application prospects.
[0075] The hollow silica microspheres and their preparation method will be further described below through specific embodiments. However, those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions in the embodiments were performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0076] Example 1
[0077] 5g of polyvinyl alcohol (PVA) was dissolved in 100g of water and stirred thoroughly at 300rpm / min to disperse it evenly. The mixture was then heated to 80℃ to obtain a 5% PVA aqueous solution. 1g of 1mol / L acrylic acid solution and 0.1g of potassium persulfate (KPS) initiator were then added and thoroughly mixed. Subsequently, 0.5mol / L sodium azide solution was added, and the reaction was carried out at 80℃ for 10h. The molar ratio of PVA to sodium azide, KPS, and acrylic acid was 1:200:400:1000, and the concentration of PVA in the reaction system was 20mol / L. After the reaction was completed, the mixture was washed four times with deionized water and dried in a vacuum drying oven at 60℃ for 6h to obtain high-purity azido-modified polyvinyl alcohol. Finally, the obtained azido-modified polyvinyl alcohol was dissolved in dichloromethane to a concentration of 5g / L.
[0078] 10 g of trichlorosilane (SiCl3H) and 50 g of anhydrous ethanol were added to a 250 mL Erlenmeyer flask and stirred at 300 rpm / min until homogeneous. Then, 0.2 g of boron trifluoride diethyl ether complex was slowly added as a catalyst, and the mixture was reacted at 60 °C for 10 h. After the reaction was completed, the mixture was cooled to room temperature and washed four times with deionized water to remove unreacted raw materials and byproducts. The reaction product was then reacted with lithium aluminum hydride (LiAlH4) at room temperature for 4 h. Finally, the mixture was added to ice water for hydrolysis, and the organic layer was separated to obtain alkynyl-containing silane-bis(trimethylsilyl)acetylene.
[0079] 200g of azide-modified polyvinyl alcohol in dichloromethane was placed in a 500mL Erlenmeyer flask, and then 175g of bis(trimethylsilyl)acetylene was added and stirred at 300rpm / min until homogeneous. Subsequently, 4g of CuSO4 was added and the mixture was allowed to react at room temperature for 20h. The molar ratio of azide-modified polyvinyl alcohol to bis(trimethylsilyl)acetylene and CuSO4 was 1:10:0.01, and the molar ratio of azide groups to acetylene groups was 1:10. After the reaction, the mixture was washed four times with deionized water and dried in a vacuum drying oven at 60℃ to obtain the product. 20g of the product was dispersed in 200g of water, and 3g of 35wt% ammonia was added to adjust the pH to 11. The mixture was reacted at room temperature for 12h to hydrolyze and condense the silane on the surface of the product to coat the PVA surface, thus obtaining SiO2@PVA microspheres. The obtained SiO2@PVA microspheres were then washed three times with water and ethanol, and dried at 60°C. The dried SiO2@PVA microspheres were then calcined at 550°C in air for 4 hours to obtain hollow silica microspheres.
[0080] like Figure 1 , Figure 2The images shown are SEM and TEM images of the hollow silica microspheres prepared in Example 1. It can be seen that Example 1 effectively prepared uniform hollow silica microspheres, although crack-like defects were present on their surface. Figure 3 As shown, Figure 3 (a) is the nitrogen adsorption-desorption curve of the hollow silica microspheres prepared in Example 1. Figure 3 (b) is a pore size distribution diagram of the hollow silica microspheres prepared in Example 1, showing that the specific surface area of the hollow silica microspheres is 90 m². 2 / g, with a pore size of 1nm~1.8nm.
[0081] Example 2
[0082] The difference between Example 2 and Example 1 is that 200g of azide-modified polyvinyl alcohol in dichloromethane solution was placed in a 500mL Erlenmeyer flask, and then 200g of bis(trimethylsilyl)acetylene was added. The mixture was stirred at 300rpm / min until homogeneous, and then 4g of CuSO4 was added to react at room temperature for 20h. The molar ratio of azide-modified polyvinyl alcohol to bis(trimethylsilyl)acetylene and CuSO4 was 1:10:0.01, and the molar ratio of azide group to acetylene group was 1:10. After the reaction, the product was washed four times with deionized water and dried in a vacuum drying oven at 60℃ to obtain the product. 20g of the product was dispersed in 200g of water, and 3g of 35wt% ammonia was added to adjust the pH to 11. The product was reacted at room temperature for 12h to hydrolyze and condense the silane on the surface of the product to coat the PVA surface, thus obtaining SiO2@PVA microspheres. The obtained SiO2@PVA microspheres were then washed three times with water and ethanol, and dried at 60°C. The dried SiO2@PVA microspheres were then calcined at 550°C in air for 4 hours to obtain hollow silica microspheres.
[0083] Based on the SEM and TEM characterization of the hollow silica microspheres in Example 2, it was found that Example 2 effectively prepared uniform hollow silica microspheres with crack-like defects on their surface.
[0084] Example 3
[0085] The difference between Example 3 and Example 1 is that 5g of polyethylene glycol (PEG) was dissolved in 100g of water and stirred thoroughly at 300rpm / min to disperse it evenly. The solution was then heated to 80°C to obtain a 5% PEG aqueous solution. Then, 1g of 1mol / L acrylic acid solution and 0.1g of KPS initiator were added and mixed thoroughly. Subsequently, 0.5mol / L sodium azide solution was added, and the reaction was carried out at 80°C for 10h. The molar ratio of PEG to sodium azide, KPS, and acrylic acid was 1:150:300:1000, and the concentration of PEG in the reaction system was 50mol / L. After the reaction was completed, the solution was washed four times with deionized water and dried in a vacuum drying oven at 60°C for 6h to obtain high-purity azido-modified polyvinyl alcohol. Finally, the obtained azido-modified polyvinyl alcohol was dissolved in dichloromethane to a concentration of 5g / L.
[0086] Based on the SEM and TEM characterization of the hollow silica microspheres in Example 3, it was found that Example 3 effectively prepared uniform hollow silica microspheres with smooth and defect-free surfaces.
[0087] Example 4
[0088] The difference between Example 4 and Example 3 is that the click chemistry catalyst used is tris(benzotriazol-1-ylmethyl)amine-copper.
[0089] Based on the SEM and TEM characterization of the hollow silica microspheres in Example 4, it was found that Example 4 effectively prepared uniform hollow silica microspheres with smooth and defect-free surfaces.
[0090] Example 5
[0091] The difference between Example 5 and Example 1 is that in the step of preparing the azide-modified polymer, the polymer used is polymethyl methacrylate (PMMA), the initiator is ammonium persulfate, and the organic solvent is styrene. The molar ratio of polymer to azide salt, initiator, and organic solvent is 1:100:100:1000, and the concentration of polymer in the grafting reaction system is 100 mol / L.
[0092] In the preparation of hollow silica microspheres, the dried SiO2@PMMA microspheres were fully dissolved and immersed in acetone, and stirred at 500 rpm / min for 12 h to allow the acetone to fully penetrate into the polymer template and dissolve the polymer. After the polymer template was completely dissolved, the silica layer was removed. The silica layer was then washed with a large amount of deionized water to remove residual acetone and dissolved PMMA. Finally, the washed silica layer was dried to obtain the hollow silica microspheres.
[0093] Based on the SEM and TEM characterization of the hollow silica microspheres in Example 5, it was found that Example 5 effectively prepared uniform hollow silica microspheres.
[0094] Example 6
[0095] The difference between Example 6 and Example 1 is that, in the click chemical reaction step, the alkynyl-containing silane used is alkynyl polyethylene glycol silane, and the molar ratio of azide-modified polyvinyl alcohol to alkynyl polyethylene glycol silane and CuSO4 is 1:20:0.1, and the molar ratio of azide and alkynyl is 1:20.
[0096] Based on the SEM and TEM characterization of the hollow silica microspheres in Example 6, it was found that Example 6 effectively prepared uniform hollow silica microspheres.
[0097] Comparative Example 1
[0098] The difference between Comparative Example 1 and Example 1 is that the alkynyl-containing silane was replaced with tetraethoxysilane (TEOS).
[0099] TEM image of the product obtained in Comparative Example 1 is shown below. Figure 4 As shown, the sphericity of silica hollow microspheres is significantly low.
[0100] Comparative Example 2
[0101] The difference between Comparative Example 2 and Example 1 is that PVA is not modified with an azide group, but is directly mixed and reacted with an alkyne-containing silane and a catalyst.
[0102] TEM characterization of the product prepared in Comparative Example 2 revealed that the spheroidization rate of the silica hollow microspheres was significantly lower.
[0103] Comparative Example 3
[0104] The difference between Comparative Example 3 and Example 1 is that no click chemistry catalyst is added in the click chemistry reaction step.
[0105] TEM characterization of the product prepared in Comparative Example 3 revealed that the spheroidization rate of the silica hollow microspheres was significantly low.
[0106] Hollow silica microspheres prepared in all examples and comparative examples were characterized. The morphology and structure of the hollow silica microspheres were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the specific surface area (BET) and pore size were tested. All test results are shown in Table 1.
[0107] Table 1
[0108]
[0109]
[0110] Combination Figures 1-4 As shown in Table 1, all embodiments of the present invention can efficiently produce hollow silica microspheres, while the comparative examples have significantly lower sphere formation rates, and the comparative examples also have smaller particle size, wall thickness, and specific surface area. Examples 1 and 2 compared the effects of different amounts of alkynyl-containing silanes added on the size, wall thickness, specific surface area, and pore size of the hollow silica microspheres. The results showed that the amount of alkynyl-containing silanes added was positively correlated with the particle size of the hollow silica microspheres, and the increase in silane amount significantly improved the density of the hollow silica sphere shells, thereby reducing the pore size. Examples 1 and 3 compared the effects of different polymer folded chains on the microsphere size and surface properties. The results showed that polyethylene glycol, as a folded chain, resulted in denser microspheres than polyvinyl alcohol. This is because polyethylene glycol decomposes at a lower temperature during calcination, thus effectively avoiding the generation of surface defects in the sphere shells. Example 1 and Example 4 compared the effects of different click chemistry catalysts on the efficiency of click chemistry reactions. The results showed that the Cu(I)-organic complex catalyst "tris(benzotriazol-1-ylmethyl)amine-copper" could increase the rate of click chemistry reactions by 50%, which could greatly shorten the reaction time and improve production efficiency. As can be seen from Example 1 and Comparative Example 1, hollow silica spheres can only be prepared efficiently when click chemistry reactions occur. If only organosilane is added, the sphere formation rate of hollow silica spheres will be significantly reduced. This is because when click chemistry reactions do not occur, the azide-treated polymer will form "clusters" in water as templates, and the hydrolyzed silane will use these as templates to coat and form hollow spheres.
[0111] In summary, the preparation method provided by this invention is characterized by mild conditions, simple process, low energy consumption, low cost, and high preparation efficiency. At the same time, it can precisely control the size, wall thickness, and density of the microspheres, effectively realizing the controllable preparation of hollow silica microspheres, which can meet the needs of different application fields.
[0112] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0113] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing hollow silica microspheres, characterized in that: The preparation method comprises the following steps: Mixing a polymer aqueous solution, an azide salt, an initiator and an organic solvent to carry out a grafting reaction to obtain an azide-modified polymer, and adding the azide-modified polymer to a polar solvent to obtain a solution of the azide-modified polymer; The alkynyl-containing silane, the azide-modified polymer solution and a click chemistry catalyst are mixed to perform a click chemistry reaction, and then an acid catalyst or a base catalyst is added to perform a hydrolysis condensation reaction to obtain a core-shell structure precursor of a silica-coated polymer; The core-shell structure precursor is subjected to a calcination treatment or a solvent extraction treatment to obtain hollow silica microspheres.
2. The method for preparing hollow silica microspheres according to claim 1, characterized in that: In the grafting reaction, the molar ratio of the polymer to the azide salt, the initiator and the organic solvent is 1:(0.5-300):(0.1-500):(50-2000); And / or, in the reaction system of the grafting reaction, the concentration of the polymer is 10 mol / L to 1000 mol / L.
3. The method for preparing hollow silica microspheres according to claim 1, characterized in that: In the solution of the azide-modified polymer, the concentration of the azide-modified polymer is 1 g / L to 10 g / L.
4. The method for preparing hollow silica microspheres according to claim 1, characterized in that: The polymer is selected from at least one of polymethyl methacrylate, polystyrene, polyethylene glycol, polyethyleneimine and polyvinyl alcohol; And / or, the initiator is at least one selected from potassium persulfate, ammonium persulfate and benzoyl peroxide; And / or, the organic solvent is at least one selected from acrylic acid, polymethyl methacrylate and styrene; And / or, the polar solvent is at least one selected from water, ethanol, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran and dichloromethane.
5. The method for preparing hollow silica microspheres according to claim 1, characterized in that: In the click chemistry reaction, the molar ratio of the azide-modified polymer to the alkynyl-containing silane and the click chemistry catalyst is 1:(0.1-20):(0.001-0.1).
6. The method for preparing hollow silica microspheres according to claim 1 or 5, characterized in that: In the click chemistry reaction, the molar ratio of the azide functional group to the alkynyl functional group is 1:0.1 to 1:
50.
7. The method for preparing hollow silica microspheres according to claim 1, characterized in that: The alkynyl-containing silane is selected from at least one of 1-(trimethylsilyl)propyne, bis(trimethylsilyl)acetylene and alkynyl polyethylene glycol silane; And / or, the click chemistry catalyst is selected from copper salts, copper complexes, ruthenium complexes, ruthenium, and azide activators.
8. The method for preparing hollow silica microspheres according to claim 1 or 7, characterized in that: The click chemistry catalyst is selected from at least one of CuSO4, CuCl2, bis(benzotriazole-1-yl) cuprous oxide, tris(benzotriazole-1-ylmethyl)amine-copper, dicyclohexenylruthenium dichloride, triphenylphosphine and ruthenium.
9. The method for preparing hollow silica microspheres according to claim 1, characterized in that: The grafting reaction temperature is 25°C to 90°C, and the time is 2h to 12h; And / or, the temperature of the click chemistry reaction is 20°C to 30°C, and the time is 12h to 24h; And / or, the calcination treatment is carried out at a temperature of 500° C. to 600° C. and for a time of 2 h to 4 h.
10. Hollow silica microspheres prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of oriented grafting modified hollow silicon spheres and LCP (Liquid Crystal Polymer) composite material
CN120988367A